(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This study explores the pedagogical significance of integrating the artistic heritage of Kamoliddin Behzod into visual arts club activities in educational institutions. The research analyzes the compositional structure, color harmony, and narrative elements of miniature painting, focusing on Behzod’s innovative contributions to this art form. By applying art historical analysis and pedagogical observation methods, the study examines how the study of miniature painting influences students’ creative thinking, aesthetic perception, and artistic skills. The findings demonstrate that incorporating Behzod’s artistic heritage into extracurricular art education enhances students’ understanding of cultural heritage and promotes the development of artistic competence.